Mesalamine-Induced Myocarditis and Coronary Vasculitis in a Pediatric Ulcerative Colitis Patient: A Case Report. (21st December 2011) - Perez-Colon, Elimarys; Dadlani, Gul H.; Wilmot, Ivan; Miller, Michelle
Abstract : Mesalamine-containing products are often a first-line treatment for ulcerative colitis. Severe adverse reactions to these products, including cardiovascular toxicity, are rarely seen in pediatric patients. We present a case of a 16-year-old boy with ulcerative colitis treated with Asacol, a mesalamine-containing product, who developed sudden onset chest pain after four weeks on therapy. Serial electrocardiograms showed nonspecific ST segment changes, an echocardiogram showed mildly decreased left ventricular systolic function with mild to moderate left ventricular dilation and coronary ectasia, and his troponins were elevated. Following Asacol discontinuation, his chest pain resolved, troponins were trending towards normal, left ventricular systolic function normalized, and coronary ectasia improved within 24 hours suggesting an Asacol-associated severe drug reaction. Mesalamine-induced cardiovascular toxicity, although rare, may represent a life-threatening disorder. Therefore, every patient presenting with acute chest pain should receive a workup to rule out this rare drug-induced disorder.